Application of Boiler Fly Ash for Oil Palm Kernel Separation in Claybath - Effendi, Zulham; Rangkuti, Ika Ucha Pradifta; Muhtadawan, Mhd. Insan (The University of Lampung, 2022)
The burning of shells and fiber as boiler fuel in palm oil mills produces waste in the form of ash which is not utilized and managed optimally, resulting in environmental damage. Based on the chemical compounds contained in fly ash, its abundant availability, its cheap price and easy-to-obtain, fly ash can be used as a cheap raw material in claybaths as a substitute for clay and calcium carbonate. This study aims to determine the effective weight of boiler ash in reducing kernel and shell production losses at the kernel processing station. This study used variations in the weight of boiler fly ash, namely 3000 g, 3500 g, 4000 g, 4500 g, and 5000 g which were tested first in the laboratory. The application of boiler ash variations that were close to the norm was tested directly in the claybath. The best weight parameter for using fly ash is found in the weight variation of B5 (5000 g) with a loss of production in the sample of 3.98% or 0.159% of the oil palm fresh fruit bunches. At the time of application, boiler fly ash should be mixed with water at a ratio of 1:2 (fly ash to water) to result the best effect. Key words : Boilers, Clay bath, Fly Ash, Kernel, Shell